Feasibility study of a mini fuel cell to detect interference from a cellular phone - M.O., Abdullah; Y.K., Gan (Elsevier B.V, 2006)
Fuel cells produce electricity without involving combustion processes. They generate no noise, vibration or air pollution and are therefore suitable for use in many vibration-free power-generating applications. In this study, a mini alkaline fuel cell signal detector system has been designed, constructed and tested. The initial results have shown the applicability of such system for used as an indicator of signal disturbance from cellular phones. A small disturbance even at 4mVcm−1, corresponding to an amplitude of 12–18mG in terms of electromagnetic field, can be well detected by such a device. Subsequently, a thermodynamics model has been developed to provide a parametric study by simulation to show the likely performance of the fuel cell alone in other environments. As such the model can provide many useful generic design data for alkaline fuel cells. Two general conclusions can be drawn from the present theoretical study: (i) fuel cell performance increases with temperature, pressure and correction factor, Cf; (ii) the temperature factor (E/T) increases with increasing temperature and with increasing pressure factor.